Giant complicated glosso-cervical arterio venous malformation managed with external carotid artery ligation and serial injection sclerotherapy: a case report and review of literature - Vishwani, Ankit; Goyal, Arun; Vaid, Divya; Gupta, Neelima; Vaid, Laxmi; Henam, Mona (International Surgery Journal, 2020)
Giant arterio venous malformation (AVM) of the tongue and floor of mouth are rare. They become life threatening when ignored by the patients. Treatment protocols are not well established. This report describes the treatment of a 35 years old female who presented to us with complains of swelling of tongue, floor of mouth and left sub mandibular region since 15 years causing dysphagia, and oral bleed since one day. Magnetic resonance Angiography revealed a giant AVM at the above site with dilated left external carotid artery (ECA) and left lingual artery. Patient underwent ECA ligation under general anaesthesia and serial injection sclerotherapy at the local site. After 3 months and 6 cycles of sclerotherapy, the patient had a satisfactory outcome. A detailed report with review of literature is presented.